Corporate Social Responsibility as a Moderator of Financial Determinants of Firm Value - Asmaranti, Ratih Dwi; Sihombing , Pardomuan (International Journal of Entrepreneurship and Business Management, 2025)
This research analyzes the influence of internal financial factors namely profitability (ROE), leverage (DER), profit growth (GR), and operational cash flow (OCF) on firm value, while assessing the moderating impact of Corporate Social Responsibility (CSR) and incorporating firm size as a control variable. The study focuses on publicly listed palm oil firms on the Indonesia Stock Exchange from 2018 to 2023. Using a quantitative approach and panel data regression, it evaluates 15 companies. Findings reveal that both the Debt to Equity Ratio (DER) and firm size significantly and negatively influence firm value, as measured by the Price to Book Value (PBV) ratio. Conversely, Return on Equity (ROE), profit growth (GR), and operating cash flow (OCF) show no significant direct impact. CSR is shown to have a significant moderating effect on the relationship between DER and firm value. These findings underscore the strategic role of CSR in mitigating the adverse effects of financial leverage, particularly in sustainability-sensitive sectors.